Evolution of Caenorhabditis elegans host defense under selection by the bacterial parasite Serratia marcescens. - McKenna J Penley; Giang T Ha; Levi T Morran (PLoS ONE, 2017)
Parasites can impose strong selection on hosts. In response, some host populations have adapted via the evolution of defenses that prevent or impede infection by parasites. However, host populations have also evolved life history shifts that maximize host fitness despite infection. Outcrossing and self-fertilization can have contrasting effects on evolutionary trajectories of host populations. While selfing and outcrossing are known to affect the rate at which host populations adapt in response to parasites, these mating systems may also influence the specific traits that underlie adaptation to parasites. Here, we determined the role of evolved host defense versus altered life history,in mixed mating (selfing and outcrossing) and obligately outcrossing C. elegans host populations after experimental evolution with the bacterial parasite, S. marcescens. Similar to previous studies, we found that both mixed mating and obligately outcrossing host populations adapted to S. marcescens exposure, and that the obligately outcrossing populations exhibited the greatest rates of adaptation. Regardless of the host population mating system, exposure to parasites did not significantly alter reproductive timing or total fecundity over the course of experimental evolution. However, both mixed mating and obligately outcrossing host populations exhibited significantly reduced mortality rates in the presence of the parasite after experimental evolution. Therefore, adaptation in both the mixed mating and obligately outcrossing populations was driven, at least in part, by the evolution of increased host defense and not changes in host life history. Thus, the host mating system altered the rate of adaptation, but not the nature of adaptive change in the host populations.